The Dynamics of Mass Loss and Nutrient Release of Decomposing Fine Roots, Needle Litter and Standard Substrates in Hemiboreal Coniferous Forests - Kriiska, Kaie; Lõhmus, Krista; Frey, Jane; Asi, Endla; Kabral, Naima; Napa, Ülle; Ostonen, Ivika (Frontiers in Forests and Global Change, 2021)
Litter decomposition is a key process that drives carbon and nutrient cycles in forest soils. The decomposition of five different substrate types was analysed in hemiboreal coniferous forests, focusing on the mass loss and nutrient (N, P, K) release of fine roots (FR) and needle litter in relation to the initial substrate and soil chemistry. A litterbag incubation experiment with site-specific FR and needle litter and three standard substrates (green and rooibos tea, α-cellulose) was carried out in four Norway spruce and four Scots pine-dominated stands in Estonia. Substrate type was the primary driver of mass loss; while the dominant conifer species didn’t affect the decay rate of different substrates either final N-release from the litter. Αlpha-cellulose lost 98±1% of the mass in 2-years, while the FR mass loss was on average 23±2% after 3-years of decomposition. The FR decomposition rate could be predicted using a corresponding model of green tea, although the rate of FR decomposition is approximately five times lower than the rate of green tea in the first 3-years. The annual decomposition rate of the needle litter is rather constant in hemiboreal coniferous forests in the first three years. The initial substrate of fine roots or needle litter and soil chemistry jointly had a significant effect on mass loss in the later stage of decomposition. The critical N concentration for N release was lower for pine FR and needle litter (0.9–1.3% and 0.7–1.1%) compared to spruce (1.2–1.6% and 1.5–1.9%, respectively). The release rate of K depended on the initial K of substrate, while the release of N and P was significantly related to the initial C:N and N:P ratios, respectively. The results show the central role of soil and substrate initial chemistry in the decomposition of fine roots and needle litter across hemiboreal forests, especially at later stage (after two years) of decomposition. The slower decomposition and higher retention of N in the fine roots relative to needle litter suggests that fine roots have a substantial role in the carbon and nitrogen accumulation in boreal and hemiboreal forest ecosystems.